Performance and emissions characterization of diesel engine running with re-formulated palm oil methyl ester-diesel blended fuel - Husnawan, M.; Masjuki, Haji Hassan; Mahlia, Teuku Meurah Indra; Saidur, Rahman; Kalam, Md. Abul (2009)
Diesel engine emissions such as CO, NOx, THC and smoke were evaluated while the engine running with re-formulated Palm Oil Methyl Ester (POME) blended fuel. The fuel was re-formulated by additional additive and blending agent in order to get better atomization during blending process. A multi cylinder diesel engine was operated from 1000 rpm to 2500 rpm with 50% load, full throttle opening and fueled by three (3) types of fuel blends which containing 20% vol POME and 1% vol to 5% vol of additive. The additive is the combination of blending agent additive, ester stabilizer and anti-oxidation additive. The result shown that by presence of additive the emissions were decreased generally, especially for NOx and CO emission showed favorable result for POME blended additive fuel. Therefore, by re-formulating POME-diesel blended fuel could reduce poisonous gases from diesel engine combustion. In addition, the use of blended additive by proper composition is capable to increase the stability of the fuels as well as produce better combustion.